UNDERSTANDING THE READINESS OF IMPLEMENTING OUTCOME-BASED EDUCATION AMONG SELECTED HIGHER EDUCATION INSTITUTIONS IN PHILIPPINES - Mercado, Cecilia; Lagto, Harold (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
To meet the challenges of globalization, high technology, economic transformation, and international competitions in the new century, there have been numerous educational reforms and initiatives in many countries in the Asia-Pacific Region and other parts of the world (Cheng, 2005). The Philippines along with the other members of the ASEAN region are faced with these challenges. The current study has been designed to understand the readiness of selected HEIs in the Philippines as they embark to adopt a new educational system that is grounded in outcomes-based education (OBE). This quantitative study shows that these institutions are moderately familiar with the concepts, processes, and standards on OBE implementation. Among the initiatives identified to ensure the success of OBE implementation, sending of faculty for training and workshops ranked first. It shows that the HEIs strongly agree to the principle that OBE –based instructional strategies expand the motivation or purpose of technology beyond awareness and understanding levels. The identified principles supporting the level of importance in the development of OBE based instructional materials are perceived as extremely important. Internet sites are recognized as learning resources and are regarded as extremely important. The HEIs very frequently use the other forms of assessments except for direct assessment. The majority of the HEIs only very frequently use assessment practices. These results aim to assist educational leaders in addressing the areas of weaknesses in order to successfully implement OBE.